The Epoch of Universalism 1769-1989 / l'époque de L'universalisme 1769-1989. - Hofmann, Franck. (Beyond Universalism / Partager L'universel Series, 2020)
How can universality be addressed after the necessary epistemic and ethical critique of Western universalism? Building on such concepts as materiality and reparation, narration and translation, the series Beyond Universalism | Partager l'universel seeks to understand how contemporary cultural and social practices are producing a new consciousness of universality - experiences, reflections, and agencies of a shared humanity.